Effect of supplementation of zinc methionine on claw characteristics in crossbred dairy cattle - RANDHAWA, SWARAN S; DUA, K; SINGH, R S; DHALIWAL, P S; SHARMA, A K (The Indian Journal of Animal Sciences, 2012)
Lactating dairy cows (28) selected from a commercial dairy herd were stratified into 2 groups of 14 animals each by keeping approximately equal number of animals with different lameness scores in both the groups. Fourteen animals in the treatment group were supplemented with zinc methionine (ZM) for 5 months in a controlled study keeping the other 14 as untreated control. Hoof trimming was undertaken in all the dairy cows before and after the trial period. Claw lesions were examined to evaluate the effect of ZM on the frequency and severity of claw lesions. It was observed that supplementation of ZM resulted in significant decline in disease score owing to heel erosions and sole avulsions. White line hemorrhages though present in small number disappeared totally after supplementation. ZM caused a nonsignificant impact on the recurrence of overgrown soles and significant effect on corkscrew hooves. However, there was not much improvement in lameness score and rear leg view conformation. On the whole, a significant decline in number of heel erosions, sole avulsions, resolution of all the white line hemorrhages and a control on the reoccurrence of overgrowths resulted in significant decline in overall disease score in cows fed ZM. Trace mineral analysis of hooves before and after supplementation of ZM revealed a non-significant increase in hoof sole zinc status with no change in sole copper, manganese and iron levels.